Direct Synthesis of Functional Thermoplastic Elastomer with Excellent Mechanical Properties by Scandium‐Catalyzed Copolymerization of Ethylene and Fluorostyrenes. (2nd November 2021) - Wang, Tiantian; Wu, Chunji; Ji, Xiangling; Cui, Dongmei
Abstract: Herein, we report copolymerizations of ethylene (E) and ortho ‐/ meta ‐/ para ‐fluorostyrenes (S F = o FS/ m FS/ p FS) by using quinolyl methylene fluorenyl scandium complex (Flu‐CH2 ‐Qu)Sc(CH2 SiMe3 )2 . The copolymerizations proceed in a controlled fashion to afford copolymers composed of "soft" ethylene‐fluorostyurene (E–S F ) random segments ( T g =−22.2–5.1 °C) and "hard" crystalline ethylene–ethylene (E–E) segments ( T m =42.3–130.2 °C). The copolymers behave like thermoplastic elastomers at room temperature by showing high stress values up to 39.5 MPa under elongation‐at‐break above 774 % with elastic recovery over 75 %. The excellent mechanical properties are mainly attributed to the microphase separation of the nanoscale crystalline E–E domain from the amorphous E–S F copolymer matrix proved by AFM, WAXD and SAXS. The mechanism investigation by the density functional theory (DFT) simulation reveals that the steric bulky and electron‐withdrawing ligand of the catalytic precursor prefers E propagation to generate long E–E segments, while the incorporation of S F is thermodynamic control. Abstract : A brand‐new functionalized thermoplastic elastomer with excellent toughness and efficient elastic recovery has been successfully achieved through the direct copolymerization of E and ortho ‐/ meta ‐/ para ‐fluorostyrene ( o FS/ m FS/ p FS) using the scandium complex. The DFT simulation reveals that the bulky and electron‐withdrawing ligand of the catalytic precursor prefers E propagation to generate long E–E segments.